SQUIDs for magnetic and electromagnetic methods in mineral exploration - Ronny Stolz; Markus Schiffler; Michael Becken; Anneke Thiede; Michael Schneider; Glenn Chubak; Paul Marsden; Ana Bra\~na Bergshjorth; Markus Schaefer; Ockert Terblanche (Mineral Economics, 2022)
Research on quantum sensors for the detection of magnetic fields (quantum magnetometers) is one of the fast-moving areas of Quantum Technologies. Since there exist expectations about their use in geophysics, this work will provide a brief overview on the various developing quantum technologies and their individual state of the art for implementing quantum magnetometers. As one example, the developments on superconducting quantum interference devices, so-called SQUIDs as a specific implementation of a quantum magnetometer, are presented. In the course of this, SQUID instrument implementations and associated demonstrations and case studies will be presented. An airborne vector magnetometer with ultra-low noise ( <10fT/Hz) and high dynamic range of >32bitwill be introduced which has the prospect to be applied for the magnetic method in parallel with electromagnetic methods such as passive audio-frequency magnetics or semi-airborne methods using active transmitters such as elongated grounded dipole sources. The according signals are separated in the frequency domain. A second implementation is an airborne full tensor gradiometer instrument will be discussed which has shown already a number of successful case studies and which turned into commercial operation in the past years. Besides the airborne instrument, a very successful implementation of quantum magnetometers is the SQUID-based receiver for the ground-based transient electromagnetic method. Today it is a mature technology which has been in commercial use for more than a decade and has led to a number of discoveries of conductive ore bodies. One case study will be presented which demonstrates the performance of this instrument. Finally, future prospects of using quantum magnetometers, including SQUIDs and new optically pumped magnetometers, in geophysical exploration will be discussed. Particular applications for both sensor types will be introduced.
Keywords: 660; Mineral exploration; Magnetics; Electromagnetic methods; Quantum sensors; SQUID